The political role of Muslim women: between traditional texts and changing realities - Osmani, Noor Mohammad; Faruq, Abu Umar; Ali, Muhammad Yousuf (2009)
Muslim scholars are in general agreement that women are not entitled to hold the topmost public office of a nation. Is it due to Qur’anic texts and Prophetic traditions (ahadith) that women are barred from key positions or is it largely due to socio-cultural and economic settings of a country? The Qur’an urges women to stay quietly at home and not to make dazzling public displays like that of the pre-Islamic period of Jahilyia [ignorance] (33:33). It also asserts that men are the protectors and maintainers of women (4:34). The only Prophetic tradition in this regard is that the Prophet is reported to have said, “No nation will ever prosper if a woman is assigned to its highest public office.” (Bukhari, no. 4073, 6570). On the other hand, since the Qur’an acclaims the Queen of Sheba for her just rule, such prominent scholars as Imam Abu Hanifah, Tabari and Ibn Hazm support that women could hold the topmost judicial position. Ibn Hazm also asserts that there is no theoretical prohibition for women to carry out the mission of Prophethood. Naturally, if they could be Prophets, they would also be the leaders, for the Prophets are the leaders. This research aims to explore this issue and examine it objectively by primarily analyzing Qur’anic ayats, Prophetic traditions, the heritage of Islamic Caliphs and the verdicts of Muslim jurists. The paper will critically evaluate the validity of the quoted hadith, and examine its circumstances in order to understand how and why the Prophet would have said such a hadith. This analysis is crucial to address present day realities, as a significant number of Muslim women have successfully led their nations toward prosperity by holding topmost offices. Finally, this presentation hopes to shed light on what the real political status of Muslim women should be today in light of the Qur’an, traditional texts and sound realities?